Vitamin C supplementation and upper respiratory tract infections in marathon runners - Himmelstein, S. A.; Robergs, R. A.; Koehler, K. M.; Lewis, S. L.; Qualls, C. R. (Journal of Exercise Physiology online, 1998)
This study was funded in part by a grant from the University of New Mexico Clinical Research Center: MO1-RR-00997 1994, and from the University of New Mexico, College of Education, 1994 Graduate Research, Project and Travel Grant. ABSTRACT The purpose of this study was to determine whether vitamin C supplementation reduces the incidence of upper respiratory tract infections (URTIs), and attempt to explain the variability in URTIs among marathon runners and sedentary subjects. Marathon runners (n=44) and sedentary subjects (n=48) were randomly assigned either 1,000 mg vitamin C or a placebo daily for two months prior to and one month following a marathon race. Baseline (pre-supplementation) plasma vitamin C concentrations were higher among the vitamin C treated runners (VR, n=30) and placebo treated runners (PR, n=14) (78.5 ±2.7 and 84.0 ±3.6 mmol/L, respectively) compared to vitamin C treated sedentary (VS, n=23) and placebo treated sedentary (PS, n=25) subjects (61.1±4.7 and 52.8 ±5.0 mmol/L, respectively). Vitamin C concentrations increased with supplementation (81.0±2.1 mmol/L for VR and 72.6 ±2.9 mmol/L for VS). No treatment differences were found for URTI incidence (33.3%, 42.9%, 43.5%, and 32.0% among VR, PR, VS, and PS, respectively). Multiple logistic regression revealed the following factors to be significantly related to an increased risk of URTIs: (1) faster training pace, (2) greater number of marathons run, (3) shorter distance for the longest run of the week, and (4) female gender. The data indicate that vitamin C supplementation of 1,000 mg/day did not decrease the incidence of URTIs in marathon runners. Training and gender were more influential than vitamin C supplementation in explaining the incidence of URTIs. ABSTRACT FROM AUTHOR